Extremely-low frequency magnetic field effects on sulfate reducing bacteria viability - Fojt, Lukáš; Strašák, Luděk; Vetterl, Vladimír (Electromagnetic biology and medicine, 2010)
50 Hz magnetic fields effects on Sulfate Reducing Bacteria (SRB) viability were studied by colony forming units (CFU) counting. We found a 15% decrease of CFU number after magnetic field exposure (B=7.1 mT, f=50 Hz, t=24 min) compared to the control samples. These results are in good agreement with our previous work on other bacterial strains. The magnetic field effects on SRB are relatively large for small magnetic fields. The data correlations have been subjected to a simple physical chemical analysis, yielding surprisingly large estimates for the characteristic magnetic reaction susceptibility, even when the entire bacterium is assumed to be the direct target of interaction of the magnetic ac fields for the exposures in the time range from 3-24 min.
Keywords: Sulfates; sírany; oxidace-redukce; Kinetics; Colony Count, Microbial; počet mikrobiálních kolonií; Electromagnetic Fields; Oxidation-Reduction; mikrobiální viabilita; Bacteria; Microbial Viability; kinetika; elektromagnetická pole